Design and optimization of inner-rotation nozzle in negative pressure duster. (October 2019) - Guodong, Zhai; Cong, Ren; Wei, Tong
This article proposes a design and experimental method of a new inner-rotation nozzle. First, the design model of the inner-rotation nozzle was established based on Abramovich's maximum flow principle and high-pressure water jet crushing theory. Considering the specific conditions of the negative pressure duster, the reference values of nozzle structure parameters are calculated. The simulation is conducted for studying the relationship between the nozzle's structure parameters and its performance including water flow velocity at nozzle outlet, atomization effects, and so on. By orthogonal experiment, the reasonable nozzle structure parameters were obtained by analyzing the speed of flow, the amount of air, and so on. Then, a series of nozzles were machined with different size shells and cores. In order to select out the optimum matching of nozzle cores and shells, an experimental system is established. Considering the installation location, wind speed, liquid–gas ratio, and other factors, the optimum matching of the shell core was chosen. At the same time, the application test of the negative pressure duster was carried out on the fully mechanized mining face. The research results show that the removal rate of pulverized coal has a higher improvement, and provides a theoretical basis for the design of negative pressure duster.